Novel Mycobacterium Related to Mycobacterium triplex as a Cause of Cervical Lymphadenitis - Hazra, Rohan (American Society for Microbiology, 2001)
The Mycobacterium avium complex (MAC) is an important cause of cervical lymphadenitis in children, and its incidence appears to be increasing in the United States and elsewhere. In areas where Mycobacterium tuberculosis is not prevalent, M. avium causes the vast majority of cases of mycobacterial lymphadenitis, although several other nontuberculous mycobacterial species have been reported as etiologic agents. This report describes the case of a child with cervical lymphadenitis caused by a nontuberculous mycobacterium that could not be identified using standard methods, including biochemical reactions and genetic probes. Direct 16S ribosomal DNA sequencing showed greater than 99% homology with Mycobacterium triplex, but sequence analysis of the 283-bp 16S-23S internal transcribed spacer (ITS) sequence showed only 95% identity, suggesting that it is a novel species or subspecies within a complex of organisms that includes M. triplex. Mycolic acid high-performance liquid chromatography analysis also identified this isolate as distinct from M. triplex, and differences in susceptibility to streptomycin and rifampin between this strain and M. triplex were also observed. These data support the value of further testing of clinical isolates that test negative with the MAC nucleic acid probes and suggest that standard methods used for the identification of mycobacteria may underestimate the complexity of the genus Mycobacterium. ITS sequence analysis may be useful in this setting because it is easy to perform and is able to distinguish closely related species and subspecies. This level of discrimination may have significant clinical ramifications, as closely related organisms may have different antibiotic susceptibility patterns.